2021
DOI: 10.1016/j.jacbts.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Results in Long-Term Diastolic Dysfunction That Is Prevented by Histone Deacetylase Inhibition

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 68 publications
(56 reference statements)
5
41
0
Order By: Relevance
“…In an experimental AKI model, mice developed diastolic dysfunction with reduced EF ( Hu et al, 2017 ). However, other authors have shown more recently that AKI mice develop HF with preserved EF ( Fox et al, 2019 ; Soranno et al, 2021 ). In spite of the differences observed, which are possibly based on the method used to induce renal disease and the time of renal damage progression, renal disease mouse models have clearly shown HF development.…”
Section: Cardiovascular Events and Mortality In Renal Diseasementioning
confidence: 99%
“…In an experimental AKI model, mice developed diastolic dysfunction with reduced EF ( Hu et al, 2017 ). However, other authors have shown more recently that AKI mice develop HF with preserved EF ( Fox et al, 2019 ; Soranno et al, 2021 ). In spite of the differences observed, which are possibly based on the method used to induce renal disease and the time of renal damage progression, renal disease mouse models have clearly shown HF development.…”
Section: Cardiovascular Events and Mortality In Renal Diseasementioning
confidence: 99%
“…CRS classification is denoted by the principal organ dysfunction by temporal sequence and the relative acuity of each illness [30,31]. AKI may lead to diastolic dysfunction within 72 h, but it can persist up to 12 months after AKI, suggesting that systemic effects during the initial AKI episode are likely contributors to long term cardiovascular disease [1,32]. AKI produces systemic effects that increase inflammation, cardiac dysfunction, and metabolic disorders, such as reducing adenosine 5 -triphosphate (ATP) formation in the heart [32].…”
Section: Cisplatin-induced Aki and The Cardiorenal Associationmentioning
confidence: 99%
“…AKI may lead to diastolic dysfunction within 72 h, but it can persist up to 12 months after AKI, suggesting that systemic effects during the initial AKI episode are likely contributors to long term cardiovascular disease [1,32]. AKI produces systemic effects that increase inflammation, cardiac dysfunction, and metabolic disorders, such as reducing adenosine 5 -triphosphate (ATP) formation in the heart [32]. Cardiotoxic manifestations also include heart failure, angina, acute myocardial infarction, thromboembolic events, autonomic cardiovascular dysfunction, hypertension and hypotension, and severe congestive cardiomyopathy [33].…”
Section: Cisplatin-induced Aki and The Cardiorenal Associationmentioning
confidence: 99%
See 2 more Smart Citations